Golimumab for the treatment of ulcerative colitis. (3rd July 2017) - Flamant, Mathurin; Paul, Stephane; Roblin, Xavier
ABSTRACT: Introduction : Tumor necrosis factor antagonists have revolutionized the therapeutic management of inflammatory bowel disease. Infliximab and adalimumab were the first biological agents used to induce and maintain remission in ulcerative colitis. More recently, a third tumor necrosis factor antagonist, golimumab, was approved, extending the therapeutic approach for moderate-to-severe ulcerative colitis. Areas covered : In this review, the authors review the literature on the efficacy and safety of golimumab in the context of other anti-TNF agents used in the treatment of this disease. The role of therapeutic drug monitoring in the case of loss of response to an anti-TNF agent is also discussed. Expert opinion : Golimumab is currently effective to induce and maintain remission in patients with ulcerative colitis, especially those patients who are naive for an anti-TNF agent. No large studies have evaluated the efficacy of golimumab after failure of a first-line TNF antagonist therapy. In the case of loss of response to a first anti-TNF agent, therapeutic drug monitoring is essential to determine the most suitable therapeutic option.